Ameliorative Effect of Hovenia dulcis Fruit Pedicel Polysaccharides on Alcohol-Induced Intestinal Injury in Mice Investigated Using 16S rRNA Sequencing and Metabolomics - ZHANG Yuchao, ZHU Sijie, LIU Liangyu, WANG Jianyun, ZHANG Jiaxin, SU Zexiong, CHEN Jiangyan, LIU Xudong (Shipin Kexue)
This study aimed to explore the ameliorative effect of Hovenia dulcis fruit pedicel polysaccharides (HDPs) on intestinal injury in alcohol-exposed mice. Using high-throughput 16S rRNA gene sequencing technology and metabolomics, we investigated the impacts of HDPs on the gut microbiota and metabolic profile of mice with alcohol-induced intestinal injury. Additionally, enzyme-linked immunosorbent assay (ELISA), immunohistochemistry, real-time quantitative polymerase chain reaction (qPCR), and Western blot were employed to detect the changes in the expression of intestinal inflammatory factors, tight junction proteins, bile acid metabolism-related genes and proteins. The results indicated that HDPs significantly reduced the levels of pro-inflammatory factors such as interleukin-4 (IL-4), interferon-gamma (IFN-γ), and tumor necrosis factor-α (TNF-α) in mice with intestinal injury induced by alcohol, decreased the levels of lipopolysaccharide (LPS) and lipopolysaccharide binding protein (LBP), increased the level of α-amylase (AMS), and upregulated the tight junction protein Claudin 1, thereby improving intestinal barrier function. 16S rRNA sequencing revealed that compared to mice gavaged with alcohol at 114 µL/20 g mb, HDPs increased the abundance of the Lactobacillus genus and reduced alcohol exposure-induced disorders in gut microbiota diversity and structure. Metabolomics analysis found that HDPs could regulate bile acid metabolism and reduce the levels of bile acids (especially taurocholic acid and chenodeoxycholic acid) in the intestine of alcohol-exposed mice. Furthermore, HDPs inhibited the mRNA and protein expression of apical sodium-dependent bile acid transporter (ASBT) in the intestine of alcohol-exposed mice, thus reducing the absorption of bile acids and alleviating the negative impact of alcohol on the intestine. In summary, HDPs has the potential to ameliorate alcohol-induced intestinal damage by improving intestinal barrier function through the modulation of the gut microbiota and bile acid metabolism. This finding will provide a new perspective and theoretical basis for the application of HDPs in functional foods.